2014
DOI: 10.3171/2013.8.jns13608
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of lenticulostriate artery aneurysms

Abstract: The authors report on 3 rare cases of ruptured lenticulostriate artery (LSA) aneurysms that were heralded by deep cerebral hematomas. The hematomas were unilateral in 2 cases and bilateral in 1; in the bilateral case, only a single LSA aneurysm could be identified on the right side of the brain. Because of their small size (≤ 2 mm), fusiform aspect, and deep location within the brain, all of the aneurysms were treated conservatively. There was no hemorrhage recurrence, and followup angiography demonstrated spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Previous reports described that spontaneous obstruction was observed between 5 days and 2 years. [ 7 8 13 18 43 44 ] In our case, the aneurysm disappeared in a relatively early period compared with previously reported cases. The aneurysm was located at the distal portion of this thin artery, and blood flow in the artery might be weak compared with that of the main arteries.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous reports described that spontaneous obstruction was observed between 5 days and 2 years. [ 7 8 13 18 43 44 ] In our case, the aneurysm disappeared in a relatively early period compared with previously reported cases. The aneurysm was located at the distal portion of this thin artery, and blood flow in the artery might be weak compared with that of the main arteries.…”
Section: Discussionsupporting
confidence: 55%
“…[ 18 33 35 ] Among them, 52 cases of distal lenticulostriate artery aneurysms including our case are summarized in Table 1 . [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 ] Patients' ages varied from 2 months to 81 (average 41.9) years. Patients were relatively young compared to those of the cases with common saccular aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Lee A. Tan et al reported that a ruptured lenticulostriate artery aneurysm, of which fewer than 50 cases have been reported in the literature8), with the spot sign was clipped17). Other authors published a case report on endovascular treatment of a pseudoaneurysm that formed due to rupture of an anterior communicating artery aneurysm10).…”
Section: Discussionmentioning
confidence: 99%
“…If the monitored aneurysm then persists or grows in size, its occlusion should be considered. However studies are needed to strengthen this strategy [9]. Definitive treatment of LSA aneurysms involves both surgical and endovascular methods [3,8].…”
Section: Discussionmentioning
confidence: 99%